VIABILITAS BIJI KAKAO (Theobroma cacao L.) DENGAN BEBERAPA LAMA PERENDAMAN DENGAN DAGING BUAH DAN TANPA DAGING BUAH - Dede Suhendra (UNIVERSITAS LABUHANBATU, 2019)
The objective of testing some cocoa seed germination methods is to obtain information on growing ability based on sprout speed, sprout test, and vigilance. Seed germination is also influenced by the long immersion in water, the longer the soaking time germination will also be faster. The purpose of this research is to know the viability of cocoa beans to sometime immersion using meat and fruit without fruit, this research was conducted at the Laboratory of College of Agricultural Sciences of Labuhan Batu University Foundation, North Sumatera Province. This research used factorial randomized block design with 2 factors of treatment that is the long factor of immersion and flesh factor. The old factors of immersion with 6 levels are: P1 = 2 hours, P2 = 4 hours, P3 = 6 hours, P4 = 8 hours, P5 = 10 hours, P6 = 12 hours. Factor of fruit with two levels, namely: using fruit and fruitless meat. Parameters observed included germination rate (day), normal sprouts (%), abnormal germination (%), dead seed (%), vigor index (%). The results showed that the method of soaking the seeds was effective to increase the sprout growth rate without affecting the viability of cocoa sprouts. Keywords: cocoa, long immersion